SKD61과 Radical Nitriding 처리된 SKD61 기판상에 Arc Ion Plating으로 증착된 TiN 박막의 미세구조 및 기계적 특성, 마찰 및 접착력에 관한 연구 - 주윤곤(Yun-Kon Joo); 윤재홍(Jae-Hong Yoon); 방위(Wei Fang); 장세굉(Shi-Hong Zhang); 조동율(Tong-Yul Cho); 하성식(Sung-Sik Ha) (Biuletyn Uniejowski, 2007)
TiN coating on tool steel has been widely used for the improvement of durability of tools. In this work, radical nitriding(RN) is carried out on SKD61 at $450^{°}C$ for 5 hours in the ammonia gas pressure $2.7{×}10^3\;Pa$. The TiN coating is carried out by arc ion plating(AIP) with the process parameters: arc power 150 A, bias voltage -50V, coating time 40 minutes and nitrogen gas pressure $4{×}10^3\;Pa$. Hardness, elastic modulus, friction coefficient and adhesion of TiN coating on substrates of both TiN/SKD61 and TiN/RN SKD61 coatings are investigated comparatively. The primary crystalline faces of TiN surface are(200) and(111) for TiN/SKD61 and TiN/RN SKD61 respectively. In addition to the primary phase, Fe phase exists in TiN/SKD61 coating, but not in TIN/RN SKD61. The hardness of TiN/RN SKD61 is about 700 Hv, 250 Hv(56%) higher than that of TiN/SKD61 at the near interface of TiN and substrates. At the TiN surface, hardness of TiN/RN SKD61 is 2,149 Hv, 71 Hv(3%) higher than that of TiN/SKD61. The elastic modulus of TiN coating is improved to 26.7 GPa(6%) by radical nitriding. The adhesion is improved by the RN coating showing no spalling. buckling and chipping on the scratch test track which are shown on the non-RN TiN/SKD61.